The presence of Romanticism: what and how does Danny Smi-řický read? - Kowalska, Urszula (Poznańskie Studia Slawistyczne, 2011)
The main purpose of the article is to identify and recognize ways of reinterpretating romantic heritage throughout a wide historical and literary context. The thesis concentrates on a novel written by Josef Škvorecký, entitled Příběh inženýra lidských duší , which deals with the themes of the history of emigration, totalitarianism and literature, which can be helpful in elucidating unexplained experiences. It is necessary to consider dependent relationships and connections between history and older literature. The main character of Škvoreský’s story, Danny Smiřický, is a Czech emigrant working as a lecturer at a Canadian university. The experience of reading proves to him just how universal and significant literature can be. The literary works of Edgar Allan Poe and Nathaniel Hawthorne become the way of “translating” Czech experience with communism for Canadian students. An hour of literature range into an hour of history.